FC027: Uric Acid Stimulates Cytoskeleton Pathways in Vascular Smooth Muscle Cells Through F-ACTIN Polymerization and Atrogin, Αsma and SM22 up Regulation. (3rd May 2022) - Verzola, Daniela; Russo, Elisa; Bianca Bertolotto, Maria; Zanetti, Valentina; Picciotto, Daniela; Cappadona, Francesca; Esposito, Pasquale; Carbone, Federico; Montecucco, Fabrizio; Viazzi, Francesca
Abstract: BACKGROUND AND AIMS: Hyperuricaemia (HU) has been identified as a risk factor for hypertension and renal disease. The most widely documented pathogenetic mechanisms for the uric acid (UA) mediated vascular and renal damage are vascular inflammation and remodeling. Vascular smooth muscle cells (VSMCs) possess a distinctive property of plasticity that allows the phenotypic transition and contributes to vascular remodeling. The aim of this study was to investigate UA effects on VSMC cell line, focusing on phenotypic transition and searching for possible signals involved in this process. METHOD: MOVAS, a mouse VSMC cell line, was exposed for short (0–6 h) or long time (24–48 h) to 0 (No Treated cells: NT), 6, 9 and 12 mg/dL of UA, respectively. We evaluated cell viability by MTT test, migration property in a 48-well microchemotaxis chamber (using an 8 μm pore size, polycarbonate polyvinylpyrrolidone-free filters) and by phalloidin staining. Changes in cytoskeleton proteins [Smoothelin (SMT), alpha-Smooth Muscle Actin (αSMA), Smooth Muscle 22 Alpha (SM 22α)] were detected by real time polymerase chain reaction (rt-PCR) and Western blot. In addition, we evaluated angiotensin receptor 1 (AT1) and atrogin 1 expression by rt-PCR and Map kinase activation (Erk 1, 2) by western blot. Lastly, we tested the UA effects on cellular changes through a prior treatment with angiotensin receptor blockers, Valsartan (V) and Losartan (L) 10 µmol. RESULTS: A small increment in cell proliferation was observed at 24 h (+11%–15%; P < 0.05). UA promoted an increased migratory rate in UA treated VSMCs at 24 and 48 h respect to untreated cells (P < 0.001). These results were confirmed by F-actin intracellular distribution: the AlexaFluor 594-conjugate-phalloidin staining revealed a compact polymerization of F-actin in stress fibers along the major cell axis in untreated cells, while a re-arrangement in thinner and poorly oriented fibers localized at cortical level were found in UA treated cells (Fig. 1). When we evaluated cytoskeleton components, we found out that 24 h UA exposition rose up, SMT (2.5–3.4-fold; P < 0.05), αSMA (1.3–1.5-fold; P < 0.05) and SM 22α levels (1.3–2.5-fold P < 0.05). Conversely, we found a 48 h UA treatment caused them to drop (SMT = –20%–40%, P < 0.05; αSMA = –20%–40%, P < 0.05; SM 22α = –30%–43%, P < 0.05). Atrogin-1 was 2-fold up regulated at 48 h in UA treated VMSCs compared with NT (P = 0.04), suggesting a possible role for UA in cytoskeleton remodeling (Fig. 2). Furthermore, we observed a significant increase in VSMC area (+30%; P < 0.001) regardless of UA concentration and time exposition. Supposing a key role of Angiotensin involvement in UA induced VSMCs changes, AT1 expression was assessed. We found AT1 was up regulated in UA treated VSMCs compared with NT (P = 0.04). As expected, V and L had inhibitory effects on AT1 upregulation. Moreover, the two angiotensin receptors blockers inhibited all the phenotypic changes induced by UA. Lastly, UA induced a time dependent Erk 1, 2 phosphorylation (1.5–2.5-fold versus T0; P < 0.05–0.01), which was reversed by both L and V. CONCLUSION: The results of this study show for the first time as UA-induced cytoskeletal changes involve polymerization of F-actin, Atrogin, αSMA and up-regulation of SM22.These results reveal the pathways by which UA induces an increase in VSMC area and in migratory rate, suggesting UA as a key player in vascular remodeling.